A cross-sectional study: exploring the relationship between commuting time and subjective wellbeing in the UAE - Razzak, Hira Abdul; ElShamy, Amin; Harbi, Alya; AlKarbi, Mubarkah; Al Shaali, Lubna; Salama, Rasha; Alosi, Ahmed; Madi, Haifa H. N. (Frontiers in Built Environment, 2023)
Background: Commuting has become an integral part of modern life, impacting individuals' daily routines and overall well-being. The duration of commuting has been recognized as important determinants of subjective well-being, with potential implications for public health. Aim: To examine the association between commuting time and subjective well-being across the seven emirates of the UAE. Methods: A cross-sectional survey was conducted on adults aged 18 years and above, encompassing both officially employed and self-employed individuals in the UAE. The sample of 5476 participants was randomly selected from the population across the seven Emirates. To assess subjective well-being, the WHO-5 instrument, available in 31 languages and known for its ease of completion, scoring, and interpretation, was employed. Logistic regression analysis was conducted to investigate the relationship between commuting time and well-being, while controlling for individual, social, economic, and environmental factors. The adjusted odds ratios (aORs) were calculated to determine the association with poor well-being. Results: The commuting time was associated with a higher odds ratio (OR) of experiencing poor subjective well-being. This association remained consistent even after accounting for individual, social, economic, and environmental factors in the analysis models. Among employees with commuting times greater than 60 minutes, the adjusted OR of poor subjective well-being was 2.24 (95% CI, 1.82 -2.77) times higher compared to individuals with less than 15 minutes of commuting time. Similarly, for employees with commuting times between 31-60 minutes, the adjusted OR of poor subjective well-being was 1.7 (95% CI, 1.39 -2.09) times higher, while for those with commuting times between 15-30 minutes, the adjusted OR was 1.26 (95% CI, 1.04 -1.53) times higher, both compared to individuals with less than 15 minutes of commuting time. The findings indicate that commuting time plays a crucial role in determining the subjective well-being of employees in the UAE. Specifically,employees with longer commuting times tend to report lower levels of subjective well-being. This suggests a potential opportunity to implement policies aimed at reducing commuting durations, which could ultimately enhance the well-being of the employed workforce. Such measures have the potential to positively impact the mental well-being of employees in the UAE.